MICROCHIP RFID PASIVO IMPLANTADO EN DIENTES MOLARES SOMETIDOS A ALTAS TEMPERATURAS CON FINES DE IDENTIFICACIÓN FORENSE (2013)
Objective: to assess In vitro behavior of a passive RFID microchip implanted in human molars and subjected to high temperatures to determine their resistance and performance.Methods: an experimental In vitro study was done to evaluate the behavior of a passive RFID microchip (VeriChip™) implanted in 10 human molars with a composite restoration (Filtek P90™ Silorane 3M-ESPE®) in class I occlusal cavities and class V vestibular cavities and subjected to high temperatures (100 °C, 200 °C, 300 °C, 400 °C and 500 °C), in order to determine their resistance and performance. The specimens were observed through Digital Photography (DP), Stereomicroscopy (SM) and Scanning Electron Microscopy (SEM).Results: it was observed that passive RFID microchips have capacity to withstand high temperatures maintaining their macrostructural integrity, but they were observed cohesive and adhesive fractures that disrupt the mechanisms of adhesion between the dental tissues, the composite material and the microchip, and impairs its correct operation beyond 300 °C.Conclusions: passive RFID microchips implanted in human molars with a resin restoration resist the action of high temperatures without altering their macrostructure, however they only operated up to 300 °C, which eventually may contribute to the processes of forensic identification in case of burned, charred and incinerated bodies.